Post mortem outcome of organophosphorus compound poisoning cases at Mymensingh Medical College - Quader, M; Rahman, MH; Kamal, M; Ahmed, AU; Saha, SK (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):170-2. The abstract of this article is available on the PubMed website